Proceedings of the Symposium on Eye Tracking Research and Applications 2014
DOI: 10.1145/2578153.2578157
|View full text |Cite
|
Sign up to set email alerts
|

Look and lean

Abstract: Compared to the mouse, eye pointing is inaccurate. As a consequence, small objects are difficult to point by gaze alone. We suggest using a combination of eye pointing and subtle head movements to achieve accurate hands-free pointing in a conventional desktop computing environment. For tracking the head movements, we exploited information of the eye position in the eye tracker's camera view. We conducted a series of three experiments to study the potential caveats and benefits of using head movements to adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 25 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…In Eye-SeeThrough, head movement controls a toolglass that can be moved over gaze-fixated targets [29]. Other work has supplemented eye pointing with subsequent refinement of the selection by head movement [18,19,22,49]. Recently,Pinpointing compared head versus eyes as primary pointing modes, and a variety of techniques for subsequent selection refinement [23].…”
Section: Combination Of Eye and Head Movementmentioning
confidence: 99%
“…In Eye-SeeThrough, head movement controls a toolglass that can be moved over gaze-fixated targets [29]. Other work has supplemented eye pointing with subsequent refinement of the selection by head movement [18,19,22,49]. Recently,Pinpointing compared head versus eyes as primary pointing modes, and a variety of techniques for subsequent selection refinement [23].…”
Section: Combination Of Eye and Head Movementmentioning
confidence: 99%
“…Head pointing, in particular, is interesting for complementing gaze, as head movement affords stable and precise input while retaining the advantage of hands-free pointing [Bates and Istance 2003]. Head correction of gaze has been demonstrated on displays with narrow-field-of-view (FOV), where gaze shifts were assumed to be performed by the eyes alone, thus allowing head movement to be treated as independent input for relative cursor displacement [Jalaliniya et al 2015;Kurauchi et al 2015;Kytö et al 2018;Špakov et al 2014]. However, eye movement research has shown that only small gaze shifts are performed solely with eye movement, whereas more significant shifts naturally feature head movement to reach targets and maintain a comfortable eye-in-head position [Freedman and Sparks 2000;Land 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Eye movement-based interaction could be particularly useful in situations where other interaction modalities are not preferred or available, for instance when the user has severe motor disabilities or when the user's hands are occupied with other tasks. Although, using eye movements for interaction may not be as accurate as using hand-based controllers in VR, eye gaze can be much faster than conventional input devices (Špakov et al 2014;Sibert and Jacob 2000). By eliminating or reducing the number of hand-based gestures in VR, eye gaze-based interaction has the potential to reduce the so-called gorilla arm syndrome-arm fatigue due to prolonged hand-based midair gestures (Boring et al 2009;Cockburn et al 2011)-which has been shown to limit the amount of time users spend in VR (Jang et al 2017) .…”
Section: User Interactionmentioning
confidence: 99%
“…Various studies show that gaze-based pointing is faster than hand-based pointing as we are able to move our gaze faster to a target than our hands (Sidenmark and Gellersen 2019;Tanriverdi and Jacob 2000). However, due to inherent physiological characteristics of eye movements and technological limitations of eye tracking, eye gaze-based pointing is inaccurate compared to other common pointing interfaces such as hand-or head-based pointing (Špakov et al 2014;Hansen et al 2018;Qian and Teather 2017;Luro and Sundstedt 2019). The two main forms of inaccuracies in eye gaze-based pointing interfaces are caused by natural noise in eye tracking data and low eye tracking data quality.…”
Section: Selection and Manipulationmentioning
confidence: 99%